What are the challenges and opportunities facing Asda in dealing with returns of electrical goods? - Kosciukiewicz, Michael (2007)
Reverse logistics is a function that creates numerous problems for companies that do not realise its importance. Retailers face high volumes of returns in electrical goods mainly due to the liberal returns policy and are forced to deal with them in an appropriate way that conforms to the legislation concerning environmental protection. Therefore, to accomplish this task in the most effective and cost efficient manner, retailers must focus on a sound reverse logistics strategy that deals with the flow of goods along the reverse supply chain and a solid returns management strategy that specifically involves processing the returns and also forms part of the reverse logistics strategy. Both of these strategies have numerous opportunities for value creation and value loss, which means that it is vital for the retailer to understand how to approach the challenge and what the future prospects are.